Perkembangan Akhir Masa Anak-Anak - Tasya Alifia Izzani; Linda Yarni; Selva Octaria (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This study aims to explain the factors that influence human development from a western perspective and an Islamic perspective. The data sources we use are obtained from relevant and reliable literature, namely primary data sources that we use are developmental psychology books and secondary data sources that we use are scientific journals supporting the topic of discussion. The research method used is a qualitative method of literature study. The data analysis technique used is content analysis and core research, which aims to maintain the stability of the assessment process and anticipate misunderstanding or misinformation in this research. This research is presented with simple and easy principles, in order to make it easier for readers to understand the content and core on the factors that influence the development that we present in this research.